Pengembangan Lingkungan Sekolah untuk Melatih Kemandirian Anak TK - Ella Rifka Adhadila (Universitas Negeri Malang, 2018)
Abstract: The research goal is to develop natural cruising circuit is easy, fun and exercise independence. This natural cruising circuit utilizing the school environment modified by researchers that can be used to train the child's independence on kindergarten group A Pembina 2 Malang. The research design and development using the Borg and Gall were simplified into seven steps. Data collection techniques by observation, interviews, questionnaires, and documentation. Data analysis technique is easy to perform 90.5% of children natural cruising circuit, 97.1% of children happy doing natural cruising circuit, 100% child safe conduct natural cruising circuit, 96.2% of children self-sufficient in performing natural cruising circuit. While the overall data obtained from ahlo early childhood education has a validity value of 87.5%, a circuit 85%, and 85% expert character education. keyword: school environment, independence of children Abstrak: Penelitian ini bertujuan untuk mengembangkan lingkungan sekolah sebagai sirkuit jelajah alam yang mudah, menyenangkan dan melatih kemandirian. Penelitian ini menggunakan rancangan penelitian dan pengembangan Borg and Gall yang disederhanakan menjadi tujuh langkah. Teknik pengumpulan data dengan cara observasi, wawancara, kuesioner, dan dokumentasi. Hasil analisis data adalah 90,5% anak mudah melakukan sirkuit jelajah alam, 97,1% anak senang melakukan sirkuit jelajah alam, 100% anak aman melakukan sirkuit jelajah alam, 96,2% anak mandiri dalam melakukan sirkuit jelajah alam. Menurut ahli pembelajaran, sirkuit jelajah alam ini memiliki nilai kevalidan 87,5%, ahli sirkuit 85%, dan ahli pendidikan karakter 85%. kata kunci: lingkungan sekolah, kemandirian anak